PENGARUH PENGELOLAAN MODAL KERJA DAN STRUKTUR MODAL TERHADAP PROFITBILITAS PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Miftahul Hasanah SY; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of working capital management and capital structure on profitability in food and beverage industry companies listed on the Indonesia Stock Exchange. The ratio of working capital management as an independent variable uses working capital turnover. The capital structure ratio used as an independent variable is the debt to assets ratio (DAR) and the debt to equity ratio (DER). While profitability as the dependent variable is measured by return on investment (ROI). The data used in this study are secondary data, namely financial statements and annual reports. Sampling was done by purposive sampling, the sample used was 7 companies from 14 food and beverage industry companies listed on the Indonesia Stock Exchange. The analysis technique used is simple linear, multiple linear, coefficient of determination, t test (partial), and F test (simultaneous). Data analysis using linear regression analysis with the help of SPSS 21 software. The results showed that working capital partially (t test) did not significantly influence profitability. While the partial capital structure (t test) has a significant effect on profitability. The results of the simultaneous research (f test) show that there is a significant influence between working capital and capital structure together on profitability in food and beverage industry companies listed on the Indonesia Stock Exchange. Keywords: Working Capital, Capital Structure, Profitability